Navigating resistance in global health governance: Certification of smallpox eradication in China - Chen, Lu (Global public health, 2024)
Certification is an essential stage in disease eradication efforts, encompassing epidemiological, managerial, and political complexities. The certification of smallpox eradication in the People's Republic of China (PRC, or China) exemplifies the multifaceted nature of the certification. Despite eradicating smallpox in the early 1960s, before the Global Smallpox Eradication Programme (SEP) intensified in 1967, China was one of the last countries certified as smallpox-free by the World Health Organization (WHO) in 1979. The WHO encountered notable resistance during the certification of smallpox eradication in China. This article examines the underlying motivations propelling China's resistance, the factors that contributed to the shifts in its stance, the challenges navigated by the WHO, and the ultimate achievement of certification despite controversies surrounding its transparency and credibility. Through the case of the certification of smallpox eradication, the article provides a historical context of China's selective engagement in global health governance, emphasising the critical importance of building a trusting relationship between the WHO and its member states. It offers insights for fostering effective collaboration among diverse stakeholders driven by varied political agendas in addressing shared global health challenges such as the coronavirus disease (COVID-19) pandemic.